Management of Climatic Extremes with Focus on Floods and Droughts in Agriculture†. (6th December 2017) - Watanabe, Tsugihiro; Cullmann, Johannes; Pathak, Chandra S.; Turunen, Mika; Emami, Kamran; Ghinassi, Graziano; Siddiqi, Yasmin
Abstract: A changing climate leads to changes in the frequency, intensity, spatial extent, duration and timing of weather and climate extremes, and can result in unprecedented extremes. These climate extremes have significant impacts on human and ecological systems, which are influenced by changes in climate, vulnerability and exposure, resulting in increased fatalities and economic losses especially in developing countries. To reduce disaster risks, the global and local society or community need to assess weather and climate events with the interaction of these hazards, the exposure of society to these events and the vulnerability of the region and society to these extremes. On the other hand, the future projection of events and their impacts is expected to be more uncertain. Under the given uncertainties in climate change impact projections, improving resilience by reinforcing the capability of societies to cope better with extreme events is one of the most favoured approaches. The adaptation includes practical measures that not only reduce the disaster risk but also reinforce the base system. This paper aims at summarizing the current practices of managing extreme climate events, assessment of impact under climate change scenarios, and development of adaptation strategies. Copyright © 2017 John Wiley & Sons, Ltd.